Standardized ileal digestibility of amino acids in cereal grains and co-products in growing pigs - Lee, Su A (Asian-Australas J Anim Sci, 2020)
OBJECTIVE: The objective was to determine standardized ileal digestibility (SID) of crude protein (CP) and amino acids (AA) in cereal grains and various co-products fed to growing pigs. METHODS: Ten feed ingredients tested were barley (9.3% CP), lupin kernels (31.1% CP), and wheat (11.3% CP) as cereal grains, and 2 sources of corn gluten feed produced in China (21.6% CP) and Korea (24.6% CP), corn gluten meal (65.3% CP), lupin hulls (11.6% CP), rice bran (14.5% CP), soybean meal (44.8% CP), and wheat bran (15.4% CP) as co-products. Ten experimental diets were formulated to contain each ingredient as a sole source of N and an N-free diet was used to correct basal endogenous losses of CP and AA. All diets also contained 0.5% Cr(2)O(3) as an indigestible index. A replicated 11×6 incomplete Latin square design with 11 dietary treatments, 6 periods, and 22 animals was employed. Twenty-two barrows with an initial body weight of 64.6±4.9 kg were equipped with a T-cannula in the distal ileum. An experimental period consisted of a 4-d adaptation period and a 2-d collection period. RESULTS: The SID of CP in the barley, lupin kernels, wheat, 2 sources of corn gluten feed, corn gluten meal, lupin hulls, rice bran, soybean meal, and wheat bran were 84.7%, 90.5%, 90.4%, 77.4%, 74.6%, 89.5%, 90.4%, 74.4%, 86.9%, and 63.4% (standard error of the mean [SEM] = 5.3, p = 0.006), respectively. The respective SID values of Lys were 75.5%, 88.4%, 83.9%, 74.7%, 62.4%, 80.3%, 83.9%, 78.5%, 88.0%, and 71.2% (SEM = 3.3, p<0.001), and the SID values of Met were 83.6%, 88.7%, 89.4%, 85.7%, 78.3%, 88.9%, 89.4%, 85.3%, 91.1%, and 77.0% (SEM = 2.4, p<0.001), respectively. CONCLUSION: The ileal digestibility of protein and amino acids varies among the feed ingredients fed to pigs.